Second-generation colon capsule endoscopy vs. colonoscopy in pediatric ulcerative colitis: a pilot study - Oliva, Salvatore; Di Nardo, Giovanni; Hassan, Cesare; Spada, Cristiano; Aloi, Marina; Ferrari, Federica; Redler, Adriano; Costamagna, Guido; Cucchiara, Salvatore (Endoscopy, 2014)
Background and study aims: Second-generation colon capsule endoscopy (CCE-2) may overcome the invasiveness of colonoscopy in the evaluation of mucosal inflammation, especially in pediatric ulcerative colitis. The aim of this pilot study was to determine the diagnostic accuracy of CCE-2 in evaluating disease activity, using colonoscopy as a gold standard. Disease extent, tolerability, interobserver agreement, and safety were also evaluated.Methods: A total of 30 consecutive pediatric patients with ulcerative colitis were prospectively enrolled (mean age 14.1 ± 3.2 years). Patients underwent CCE-2 followed by colonoscopy in the late afternoon or the following day. The blinded procedures were performed, and the diagnostic accuracy of CCE-2 to assess disease activity was determined using a modified Matts score, which classified patients as either normal (Matts score ≤ 6) or with active inflammation (Matts score > 6). Interobserver agreement was assessed using the kappa statistic.Results: One patient was excluded from the analysis because they were unable to swallow the capsule, leaving 29 patients available for analysis. The sensitivity of CCE-2 for disease activity was 96 % (95 % confidence interval [CI] 79 – 99) and specificity was 100 % (95 %CI 61 – 100). The positive and negative predictive values of CCE-2 were 100 % (95 %CI 85 – 100) and 85 % (95 %CI 49 – 97), respectively. No serious adverse events were reported. CCE-2 had a higher overall tolerability than colonoscopy (P < 0.05). Interobserver agreement was excellent in all cases (κ > 0.86).Conclusions: Using a modified Matts score, CCE-2 was accurate in evaluating significant mucosal inflammation in children with ulcerative colitis.Trial registration:ClinicalTrials.gov – NCT01740349